The CARMA-NRO Orion survey: core emergence and kinematics in the Orion A Cloud - Kong, Shuo; Arce, Héctor G.; Sargent, Anneila I.; Mairs, Steve; Klessen, Ralf S.; Bally, John; Padoan, Paolo; Smith, Rowan J.; Maureira, María José; Carpenter, John M.; Ginsburg, Adam; Stutz, Amelia M.; et al. (The astrophysical journal, 2019)
We have investigated the formation and kinematics of submillimeter (submm) continuum cores in the Orion A molecular cloud. A comparison between submm continuum and near-infrared extinction shows a continuum core detection threshold of A V ∼ 5-10 mag. The threshold is similar to the star formation extinction threshold of A V ∼ 7 mag proposed by recent work, suggesting a universal star formation extinction threshold among clouds within 500 pc to the Sun. A comparison between the Orion A cloud and a massive infrared dark cloud G28.37+0.07 indicates that Orion A produces more dense gas within the extinction range 15 mag ≲ A V ≲ 60 mag. Using data from the CARMA-NRO Orion Survey, we find that dense cores in the integral-shaped filament (ISF) show subsonic core-to-envelope velocity dispersion that is significantly less than the local envelope line dispersion, similar to what has been found in nearby clouds. Dynamical analysis indicates that the cores are bound to the ISF. An oscillatory core-to-envelope motion is detected along the ISF. Its origin is to be further explored.
Gesehen am 08.04.2020